Seasonal environmental changes affect differently the physiological and biochemical responses of two Limonium species in Sabkha biotope. Issue 4 (11th May 2021) - Maaloul, Sameh; Abdellaoui, Raoudha; Mahmoudi, Maher; Bouhamda, Talel; Bakhshandeh, Esmaeil; Boughalleb, Fayçal
Abstract: To cope with abiotic stresses, the halophytes use various tolerance mechanisms that are not all known for some species of halophytes. This work aimed to model the responses of two halophytes, Limonium pruinosum and Limonium tunetanum, to changing environmental conditions over a year in Sabkha biotope, Tunisia. Our findings indicated that the model could describe well the seasonal variations of all studied traits over a year in this region ( R 2 > 0.80). The pH, electrical conductivity (EC), and mineral composition (i.e., Sodium [Na + ], potassium [K + ], calcium [Ca 2+ ], and magnesium [Mg 2+ ] concentrations] in the soil significantly varied during the year ( P < 0.01). The highest soil Na + concentration was found during the dry period (June–August), which matched with a high Na + content in the aerial parts (i.e., 2455.1 and 3366.0 μmol g −1 SDM in August for L. pruinosum and L. tunetanum, respectively). This accumulation is concomitant with a deficit in nutrients, particularly K + and Mg 2+ and, to a lesser extent, Ca 2+ . Following these disturbances, both species decreased their photosynthetic activity, water potential as well as the relative water content to a lesser extent, especially in August. To counteract these harmful effects, these species have accumulated organic substances, but in a different way. Indeed, L. pruinosum accumulated sucrose, fructose, and citrate, while L. tunetanum accumulated sucrose, xylitol, citrate, and malate, indicating a major role of these osmolytes in the stress tolerance mechanisms. In both species, the results also showed that all traits were highly correlated with the edaphic variables (i.e., pH, EC, Na +, K +, Ca 2+, and Mg 2+ concentrations) and with temperature as the climatic variable.